Review of Islamic Law on Wage Practices of Rice Plant Workers Case Study in Sangiang Village, Rancaekek District, Bandung District - Ela, Dede; Fasya, Gania; Wibawa, Ginan (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
Islam is a religion that regulates all aspects of human life in terms of worship, morals and muamalah. Muamalah is said to be closely related to humans who can change according to the times. Muamalah law is a rule that regulates the relationship between rights and obligations in social life. One form of conversion is cooperation between humans, the first party providing benefits or labor services and the other party providing work. In carrying out this activity, there will be a provision that the working party will receive compensation in the form of wages in return for the energy that has been expended. This collaboration is called an ijarah al-a'mal agreement or rental of services with personnel in fiqh literature. This research uses the Empirical Normative Legal Research Methodology, which is a research methodology that combines normative legal elements which are then supported by additional data or empirical elements. This research focuses on case studies and facts in the field. The main data source for this research was obtained from observations of transactions between workers and rice field owners. Qhe results of the research show that wages given to rice planting workers are wages paid using cash, wages given by rice field owners are handed over after they have finished their work. The difference in wages between men and women has been around for decades. A review of Islamic economic law related to providing wages to rice planting workers is not appropriate because it ignores the principles of justice contained in the principles of Islamic economic law and can give rise to social jealousy among rice planting workers